EFFECT OF POLYMERIC NANOPARTICLES OF CURCUMIN ON A549 CELL LINE - SAIKIA, TRIDEEP; LALHLENMAWIA, HAUZEL; LALDINCHHANA; ROY, PROBIN KUMAR; THANZAMI, KAWL (International Journal of Current Pharmaceutical Research, 2020)
Objective: Lung cancer cell line specially A549 is one of the most common malignant tumors. Curcumin is obtained from rhizomes of curcuma longa and does possess biological and pharmacological properties, among them anti-tumor activity is also one of the major findings. Here we try to developed a method for delivery of curcumin for cancer therapy. Methods: Due to low water solubility and bioavailability curcumin delivery designed as polymeric nanoparticles and prepared by emulsification homogenization method. Results: Characterization done by evaluating zeta size, potential, scanning electron microscopy. Release pattern also studied along with encapsulation and loading data. Nanoparticles were found to be spherical from morphological study and found to be below 200 nm. It does possess cytotoxic activity against lung cancer cell line and potent in comparison with its free from. Conclusion: We can conclude that polymeric nanoparticles are suitable form to delivery for antitumor activity and have suitable anticancer ctivity.